Psychological morbidities in adolescent and young adult blood cancer patients during curative‐intent therapy and early survivorship. Issue 6 (7th January 2016) - Muffly, Lori S.; Hlubocky, Fay J.; Khan, Niloufer; Wroblewski, Kristen; Breitenbach, Katherine; Gomez, Joseline; McNeer, Jennifer L.; Stock, Wendy; Daugherty, Christopher K.
Abstract : BACKGROUND: Adolescents and young adults (AYAs) with cancer face unique psychosocial challenges. This pilot study was aimed at describing the prevalence of psychological morbidities among AYAs with hematologic malignancies during curative‐intent therapy and early survivorship and at examining provider perceptions of psychological morbidities in their AYA patients. METHODS: Patients aged 15 to 39 years with acute leukemia, non‐Hodgkin lymphoma, or Hodgkin lymphoma who were undergoing curative‐intent therapy (on‐treatment group) or were in remission within 2 years of therapy completion (early survivors) underwent a semistructured interview that incorporated measures of anxiety, depression, and posttraumatic stress (PTS). A subset of providers (n = 15) concomitantly completed a survey for each of the first 30 patients enrolled that evaluated their perception of each subject's anxiety, depression, and PTS. RESULTS: Sixty‐one of 77 eligible AYAs participated. The median age at diagnosis was 26 years (range, 15‐39 years), 64% were male, and 59% were non‐Hispanic white. On‐treatment demographics differed significantly from early‐survivor demographics only in the median time from diagnosis to interview. Among the 61 evaluable AYAs, 23% met the criteria for anxiety, 28% met the criteria for depression, and 13% met the criteria for PTS; 46% demonstrated PTS symptomatology. Thirty‐nine percent were impaired in 1 or more psychological domains. Psychological impairments were as frequent among early survivors as AYAs on treatment. Provider perceptions did not significantly correlate with patient survey results. CONCLUSIONS: AYAs with hematologic malignancies experience substantial psychological morbidities while they are undergoing therapy and during early survivorship, with more than one‐third of the patients included in this study meeting the criteria for anxiety, depression, or traumatic stress. This psychological burden may not be accurately identified by their oncology providers. Cancer 2016;122:954–61 . © 2016 American Cancer Society . Abstract : More than one‐third of adolescents and young adults with potentially curable blood cancers suffer from significant anxiety, depression, or posttraumatic stress during both curative‐intent therapy and early survivorship. This suggests that this may be a time of heightened distress. The psychological burden of adolescents and young adults does not appear to be accurately identified by adolescent and young adult oncology providers, and this indicates a need for increased awareness in the hematology/oncology community.